EFFECT OF SACCHAROMYCES CERVISIAE ON SERUM BIOCHEMICAL PROFILE IN JAPANESE QUAILS - and L. RAM SINGH, ASHOK KUMAR DEVARASETTI, K. VENKATA RAMANA, E. SUNIL ANAND KUMAR (The Journal of Research, PJTSAU, 2019)
The objective of this study was to investigate the effect of supplementation of Dietary baker’s yeast Saccharomyces cervisiae (single cell protein) as a probiotic on biochemical profile of Japanese quails (Coturnix coturnix japonica). In this experiment a total of 96 day-old unsexed, Japanese quails were equally divided into three groups of 32 birds in each group. The standard basal diet was fed in first group (G1), 5% and 10% level of baker’s yeast was supplemented in basal diet for second group (G2) and third group (G3), respectively. Feed and water was supplied ad libitum for all the birds. At the end of the experiment blood samples were taken to determine some blood plasma constituents. The results obtained in this study showed that, supplementation of dietary baker’s yeast had positive effect on blood biochemical profile in Japanese quails.